Increased Interest in Military Tourism on Selected Examples from the Area of Northern and Northeastern Poland - Aleksandra Zienkiewicz; Tomasz Podciborski; Rafal Kaźmierczak (Communications - Scientific letters of the University of Zilina, 2021)
Military tourism is one of the forms of tourism that is not sufficiently researched throughout Poland. It is only in recent years, after the period of political transformation, that interest in this phenomenon has been growing every year. This research has aimed to indicate the possibilities of military tourism development in northern and northeastern Poland. It includes an analysis of data concerning the Naval Museum in Gdynia, the "Wolf’s Lair" Fortress in Gierloz and an example of a military event - an air show, which took place on the premises of the 44th Airborne Museum in Gdynia. Results of the analysis of the military tourism development in northern and northeastern Poland indicate that military sites and military-themed events attract considerable tourist traffic and play an important role in the overall development of tourism.